FRI0554 Which axial magnetic resonance imaging combination is optimal for assessing activity in spondyloarthritis?. (12th June 2018) - Plier, M.; Lecouvet, F.; Michoux, N.; Stoenoiu, M.S.; Lauwerys, B.R.; Nzeusseu Toukap, A.
Abstract : Background: None Objectives: To determine the optimal axial Magnetic Resonance Imaging (MRI) combination for assessing disease activity in spondyloarthritis Methods: In this single centre cross-sectional study, patients with a known diagnosis of axial spondyloarthritis were selected. Clinical activity was defined by an Ankylosing Spondylitis Disease Activity Score-CRP (ASDAS-CRP) ≥1.3. Bone marrow oedema was quantified by the Berlin spine score and the global score for sacroiliac joints (SIJ). The ASDAS-CRP and MRI activity evaluation of the full spine and SIJ were available in the entire cohort. Receiver operating characteristic curves were done to test the performance of different MRI combinations in identifying patients with ASDAS-CRP ³ 1.3. Performance was interpreted as follows: 0.61–0.70=fair, 0.71–0.80=moderate. A pairwise comparison of the area under the curves (AUC) was made to rank these MRI scores according to their diagnostic performance. Results: 44 patients were assessed (30 were men; mean age was 37 years; mean disease duration was 5.0 years; median serum CRP level was 4.0 mg/L; mean ASDAS-CRP was 2.6; n=36 with ASDAS≥1.3, and n=8 for ASDAS<1.3). MRI activity score (MRIAS) performance was moderate for thoracic spine alone and SIJ in combination with thoracic spine or thoraco-lumbar spine or cervico-thoracic spine or total spine. Performance was fair for SIJ alone and total spine alone. MRIAS yielded the highest specificity for SIJ alone (Se=44%, Sp=100%), and the highest sensitivity for thoracic spine alone (Se=89%, Sp=50%). MRIAS for SIJ in combination with the thoracic spine yielded the highest AUC (0.78, p=0, 0002). However, no significant difference was observed between MRIAS with a moderate performance (p > 0.05, whatever AUCs comparisons). Conclusions: For assessing disease activity in axial spondyloarthritis MRI of the SIJ in combination with the thoracic spine performed as good as MRI based on a more extended imaging of the spine. Disclosure of Interest: None declared